Pengembangan Service Masking Data dengan Metode Scramble pada Sistem TXX: Studi Kasus PT XYZ - Fani Amanatul Khaliq; Wasis Haryono (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The advancement of digitalization in financial institutions demands secure system development practices, particularly regarding the use of customer data in development and UAT environments. In the TXX core system, the use of raw data without sanitization poses a potential risk of sensitive information leaks. This study aims to develop a data sanitization service using a scrambling method capable of scrambling personal data without altering the structure, format, or integrity of the testing process. The research method employs a research and development approach, comprising system analysis, database and service flow design, implementation of a TAFC-based prototype, and functional and structural testing. The implementation resulted in three main modules: Parameter Scramble, Agent Service Scramble, and Routine Service, which are integrated with PT XYZ’s development environment. Black-box testing results indicate that all interface functions and service processes operate as expected. White-box testing of the program structure ensured that the internal logic, flow control, and multithreading mechanisms operated stably without race conditions. Additionally, usability testing using the System Usability Scale on 14 respondents yielded a score of 77, which falls into the “Good” and acceptable category.